Therapeutic play to prepare children for invasive procedures: a systematic review - Rosalia Daniela Medeiros da Silva; Silvia Carréra Austregésilo; Lucas Ithamar; Luciane Soares de Lima (Elsevier, 2017)
Objective: To analyze the available evidence regarding the efficacy of using therapeutic play on behavior and anxiety in children undergoing invasive procedures. Data source: The systematic review search was performed in the MEDLINE, LILACS, CENTRAL and CINAHL databases. There was no limitation on the year or language. Synthesis of data: The literature search found 1892 articles and selected 22 for full reading. Eight articles were excluded, as they did not address the objectives assessed in this review. Twelve studies, representing 14 articles, were included. The studies were conducted between 1983 and 2015, five in Brazil, one in the United States, five in China, one in Lebanon, one in Taiwan, and one in Iran. Most studies showed that intervention with therapeutic play promotes reduction in the level of anxiety and promotes collaborative behavior and acceptance of the invasive procedure. Conclusions: Evidence related to the use of therapeutic play on anxiety and behavior of children undergoing invasive procedures is still questionable. The absence, in most studies, of the creation of a random sequence to assign the subjects to either the control or the experimental group, as well as allocation concealment, are factors that contribute to these questions. Another issue that characterizes an important source of bias is the absence of blinded evaluators. It is necessary to perform further studies that will take into account greater methodological stringency. Resumo: Objetivo: Revisar, de forma sistemática, as evidências em relação a eficácia da utilização do brinquedo terapêutico sobre o comportamento e a ansiedade de crianças submetidas a procedimentos invasivos. Fontes dos dados: A busca da revisão sistemática foi efetuada nas bases MedLine, Lilacs, CENTRAL e CINAHL. Não houve limitação quanto ao ano ou idioma. Síntese dos dados: Na busca de literatura foram encontrados 1892 artigos e selecionados 22 para leitura integral. Foram excluídos 8 artigos que não respondiam aos objetivos avaliados nesta revisão. Foram incluídos 12 estudos, correspondentes a 14 artigos. Os estudos foram conduzidos entre 1983 e 2015, cinco no Brasil, um nos Estados Unidos, cinco na China, um no Líbano, um em Taiwan e um no Irã. A maioria dos estudos mostrou que a intervenção com brinquedo terapêutico promove redução no nível de ansiedade e favorece um comportamento de colaboração e aceitação do procedimento invasivo. Conclusões: As evidências relacionadas ao uso do brinquedo terapêutico sobre a ansiedade e comportamento de crianças submetidas a procedimentos invasivos ainda são questionáveis. A ausência, na maioria dos estudos, de uma geração de sequência aleatória para direcionamento dos sujeitos para os grupos controle ou experimental e do sigilo de alocação são fatores que contribuem para este questionamento. Uma outra questão que caracteriza importante fonte de viés é o não cegamento dos avaliadores. Se faz necessário a realização de novas pesquisas que levem em consideração um maior rigor metodológico. Keywords: Children, Play and playthings, Anxiety, Behavior, Hospital care, Palavras-chave: Criança, Jogos e brinquedos, Ansiedade, Comportamento, Assistência hospitalar